Different DNA damage response of cis and trans isomers of commonly used UV filter after the exposure on adult human liver stem cells and human lymphoblastoid cells - Sharma, Anežka; Bányiová, Katarína; Babica, Pavel; El Yamani, Naouale; Collins, Andrew Richard; Čupr, Pavel (The Science of the total environment, 2017)
2-ethylhexyl 4-methoxycinnamate (EHMC), used in many categories of personal care products (PCPs), is one of the most discussed ultraviolet filters because of its endocrine-disrupting effects. EHMC is unstable in sunlight and can be transformed from trans-EHMC to emergent cis-EHMC. Toxicological studies are focusing only on trans-EHMC; thus the toxicological data for cis-EHMC are missing. In this study, the in vitro genotoxic effects of trans- and cis-EHMC on adult human liver stem cells HL1-hT1 and human-derived lymphoblastoid cells TK-6 using a high-throughput comet assay were studied. TK-6 cells treated with cis-EHMC showed a high level of DNA damage when compared to untreated cells in concentrations 1.56 to 25μgmL-1. trans-EHMC showed genotoxicity after exposure to the two highest concentrations 12.5 and 25μgmL-1. The increase in DNA damage on HL1-hT1 cells induced by cis-EHMC and trans-EHMC was detected at the concentration 25μgmL-1. The No observed adverse effect level (NOAEL, mg kg-1bwday-1) was determined using a Quantitative in vitro to in vivo extrapolation (QIVIVE) approach: NOAELtrans-EHMC=3.07, NOAELcis-EHMC=0.30 for TK-6 and NOAELtrans-EHMC=26.46, NOAELcis-EHMC=20.36 for HL1-hT1. The hazard index (HI) was evaluated by comparing the reference dose (RfD, mgkg-1bwday-1) obtained from our experimental data with the chronic daily intake (CDI) of the female population. Using comet assay experimental data with the more sensitive TK-6 cells, HIcis-EHMC was 7 times higher than HItrans-EHMC. In terms of CDI, relative contributions were; dermal exposure route>oral>inhalation. According to our results we recommend the RfDtrans-EHMC=0.20 and RfDcis-EHMC=0.02 for trans-EHMC and cis-EHMC, respectively, to use for human health risk assessment. The significant difference in trans-EHMC and cis-EHMC response points to the need for toxicological reevaluation and application reassessment of both isomers in PCPs.
Keywords: lymfocyty; cinnamáty; přípravky chránící proti slunci; buněčné linie; Humans; Risk Assessment; Isomerization; Cell Line; kosmetické přípravky; High-throughput comet assay; Cosmetics; trans/cis-EHMC; Lymphocytes; Cinnamates; poškození DNA; Sunlight; Sunscreening Agents; DNA Damage; Stem Cells; Human risk assessment; sluneční záření; ženské pohlaví; Genotoxicity; Liver; hodnocení rizik; kmenové buňky; lidé; játra; Adult human liver stem cells; Female